1998
DOI: 10.1074/jbc.273.27.16686
|View full text |Cite
|
Sign up to set email alerts
|

The Lutheran Blood Group Glycoproteins, the Erythroid Receptors for Laminin, Are Adhesion Molecules

Abstract: The Lutheran antigens are recently characterized glycoproteins in which the extracellular region contains five immunoglobulin like domains, suggesting some recognition function. A recent abstract suggests that the Lutheran glycoproteins (Lu gps) act as erythrocyte receptors for soluble laminin (Udani, M., Jefferson, S., Daymont, C., Zen, Q., and Telen, M. J. (1996) Blood 88, Suppl. 1, 6 (abstr.)). In the present report, we provided the definitive proof of the laminin receptor function of the Lu gps by demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 35 publications
2
129
1
Order By: Relevance
“…We have demonstrated previously that the ability to bind soluble laminin, as detected by flow cytometry, increases proportionally with B-CAM/LU expression levels of both AA and SS RBC [15]. El Nemer et al [20] further showed that recombinant soluble LutheranFc fragment inhibited 90-100% of soluble laminin binding to AA and SS RBC. Our present study of density-separated fractions of SS RBC also confirms that the ability to bind soluble laminin is correlated with B-CAM/LU expression levels in the corresponding cell fractions.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have demonstrated previously that the ability to bind soluble laminin, as detected by flow cytometry, increases proportionally with B-CAM/LU expression levels of both AA and SS RBC [15]. El Nemer et al [20] further showed that recombinant soluble LutheranFc fragment inhibited 90-100% of soluble laminin binding to AA and SS RBC. Our present study of density-separated fractions of SS RBC also confirms that the ability to bind soluble laminin is correlated with B-CAM/LU expression levels in the corresponding cell fractions.…”
Section: Discussionmentioning
confidence: 84%
“…El Nemer et al and our work showed that the ability of RBC to bind soluble laminin increases with increased expression of B-CAM/LU [20][21][22]. However, data from Lee and colleagues have suggested that HD SS RBC account for the SS RBC most adherent to immobilized laminin during continuous flow exerting the physiological shear stress of 1 dyne/cm 2 [16].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…At day 7, polarized cells were fixed 20 min with 4% paraformaldehyde, treated with 50 mM NH 4 Cl in PBS, permeabilized 10 min with 0.5% Triton (PBS) and incubated with F241 anti-Lu MoAb (1:10) and the polyclonal anti-DII-spectrin SH3 domain A c c e p t e d M a n u s c r i p t Licenced copy. Copying is not permitted, except with prior permission and as allowed by law.…”
Section: Confocal Fluorescence Microscopy and Immunofluorescence Of Tmentioning
confidence: 99%
“…10 4 mocktransfected MDCK cells or transfected cells expressing wt-Lu, mt-Lu, D343R Lu mutant or Lu(v13) were added to the wells (in 400 Pl). Cells were incubated in in serum-free medium for 90 min at 37°C in presence or absence of 1 Pg/ml per well of the cell-penetrating form of the Clostridium botulinum C3 toxin, an ADP ribosyltransferase that selectively ribosylates Rho proteins, rendering them inactive After this incubation time, cells were fixed 20 min with 4% paraformaldehyde, treated with 50 mM NH 4 Cl in PBS, permeabilized 10 min with 0.5% Triton (PBS), saturated 30 min in Image-iTFX signal enhancer solution. Cells were washed with PBS-0.5% BSA and incubated with Phalloidin AlexaFluor® 488 (1:50) for 1 h at RT.…”
Section: Confocal Fluorescence Microscopy and Immunofluorescence Of Tmentioning
confidence: 99%